Mass cytometry and single-cell RNA sequencing reveal immune cell characteristics of active and inactive phases of Crohn’s disease - Lin, Wenjia; Liu, Shiying; Huang, Zhuojian; Li, Haiwen; Lu, Tianyu; Luo, Yongxin; Zhong, Jiamin; Xu, Zewen; Liu, Yu; Li, Yanwu; Li, Peiwu; Xu, Qian; et al. (Frontiers in Medicine, 2023)
Background & aim For Crohn's disease (CD), the alternation of active phase and inactive phase may be related to humoral immunity and cellular immunity. This study aims to understand the characteristics of immune cells in patients with active CD (CDa) and inactive CD (CDin). Methods Mass cytometry (CyTOF) and single-cell RNA-sequencing (scRNA-seq) data about CDa, CDin and healthy control (HC) were included. CyTOF analysis was performed to capture gated subsets including T cells, T regulatory (Treg) cells, B cells, innate immune cells and natural killer (NK) cells. Differential analysis was used to identify different immune cell subsets among CDa, CDin and HC. ScRNA-seq analysis was used to verify the results of CyTOF. CD-related signaling pathways were obtained using KEGG pathway enrichment analysis. Cellchat analysis was used to infer the cell communication network among immune cell subsets. Results Compared to patients with CDin, patients with CDa had higher abundances of CD16+CD38+CD4+CXCR3+CCR6+ naive T cells, HLA-DR+CD38+IFNγ+TNF+ effector memory (EM) T cells, HLA-DR+IFNγ+ naive B cells and CD14++CD11C+IFNγ+IL1B+ monocytes. KEGG analysis showed the similarity of pathway enrichment for the above four subsets, such as thermogenesis, oxidative phosphorylation, metabolic pathways. The patients with CDin were characterize by an increased number of CD16+CD56dimCD44+HLA-DR+IL22+ NK cells. Compared to HC, patients with CDa demonstrated a low abundance of HLA-DR+CCR6+ NK cells as well as a high abundance of FOXP3+CD44+ EM Tregs. Cellchat analysis revealed the interaction network of cell subsets amplifying in CDa compared with CDin. Conclusions Some immune subsets cells were identified for CDa and CDin. These cells may be related to the ccurrence and development of CD and may provide assistance in disease diagnosis and treatment.